Investigation on vibration response characteristics and influencing factors of the fuel rods of EPR - Jiang, Naibin; Min, Guangyun; Fang, Zhengyan; Qi, Huanhuan (Frontiers in Energy Research, 2022)
First, the theory of wet modal analysis and vibration response analysis are introduced, and the semi-empirical vibration equation is derived in this article. Then, the structural models of the fuel rod of M310 and EPR are introduced, and the fuel rod is simplified to a multi-span continuous simply supported beam model subject to multi-point constraints. The fuel rod is simplified as a simply supported beam, and the springs and dimples are equivalent to elastic constraints. In addition, based on ANSYS-APDL, the wet modal analysis and response analysis of fuel rods are carried out. The modal information and transverse vibration response of the fuel rod of M310 and EPR are compared. In addition, combined with the actual operating conditions of EPR, the effects of different transverse and axial flow velocities on the transverse vibration response are discussed. Finally, different failure conditions are designed to explore the impact of clamping failure on the vibration characteristics of the fuel rod of EPR. The results have shown that compared with the fuel rod of M310, the fuel rod of EPR has a lower natural frequency and larger amplitude; the transverse flow velocity has a greater impact on the transverse vibration response; grid failure would reduce the natural frequency of fuel rods, and different positions of failure have different effects on the different-order natural frequencies of fuel rods.